Mechanical and tribological behaviour of PEEK reinforced with Sn-Zn-Bi alloy, short carbon fibres and graphene nanoplatelets - Emonde, Crystal Kayaro (2021)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia